Iron Age, Roman and Anglo-Saxon settlement along the Empingham to Hannington pipeline in Northamptonshire and Rutland - Carlyle, Simon, (Archaeopress archaeology., 2017)
This volume brings together reports on excavations by Northamtonshire Archaeology (now MOLA) in the south-east Midlands region. 19 sites were investigated, dating primarily to the Iron Age, Roman and Anglo-Saxon periods.